The Influence Of Brand Image And Sales Promotion On Purchase Decisions Mediated By Trust (Empirical Study Of Fuel Purchases At Shell Gas Stations In Jabodetabek) - Sumartono, Sumartono (Journal Research of Social Science, Economics, and Management, 2023)
This study aimed to analyze the effect of brand image and sales promotion on purchase decisions at customers of Shell gas stations mediated by Trust. This research uses a quantitative approach and Probability Sampling technique, namely random and simple samplingofo respondents. The survey was conducted to respondents withthe criteria that the respondents were customers of Shell gas stations in Jabodetabek. This research was analyzed with the Structural Equation Model (SEM) using the Smart PLS (Partial Least Square) 3.0 program. The results of the study prove that brand image has a positive and significant effecTrustTrust, other results prove that brand image has a positive and significant effect on purchase decision, sales promotion has a positive and significant effect on purchase decisTrustTrust has a positive and significant effect on purchase decision, brand image has a positive and significant effect on purchase decision mediateTrustTrust and for sales promotioTrustTrust has no positive and significant effect, then also sales promotion has no positive and significant effect on purchase decision mediateTrustTrust at Shell gas stations in Jabodetabek.